(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Levansucrase is a fructosyl transeferase, which brings hydrolytic breakdown of sucrose to glucose and fructose. The fructose was polymerized to form levan. Levan a biologically active polymer has potential application in the field of food as a low calorie sweetener, cosmetics and in pharmaceuticals as antiviral, anti- diabetic and antitumor agent. In this context the present work brought screening of 11 soil isolates for levan production. Maximum levan producing isolate (25.8g/L) was identified by 16S rRNA as Bacillus subtilis (DQ922949). Maximum enzyme activity was found to be 1250 U/ml. The optimum temperature and pH for levansucrase activity were 600C and 7.0 respectively. Enzyme showed maximum activity at 0.8M sucrose concentration. Different metal ions K+ , Mg+2, Fe+3, Mn+ , Hg+2and Ca+2 showed inhibitory effect on enzyme activity. The enzyme was partially purified by ammonium sulfate precipitation